Enveloped artificial viral capsids self-assembled from anionic β-annulus peptide and cationic lipid bilayer. Issue 52 (3rd June 2020) - Furukawa, Hiroto; Inaba, Hiroshi; Inoue, Fumihito; Sasaki, Yoshihiro; Akiyoshi, Kazunari; Matsuura, Kazunori
Abstract : We demonstrated a simple strategy for constructing enveloped artificial viral capsids by self-assembly of anionic artificial viral capsid and lipid bilayer containing cationic lipid. Abstract : Anionic artificial viral capsids were self-assembled from β-annulus-EE peptide, then complexed with lipid-bilayer-containing cationic lipids via electrostatic interaction to form enveloped artificial viral capsids. The critical aggregation concentration of the enveloped artificial viral capsid was significantly lower than that of the uncomplexed artificial viral capsid, indicating that the lipid bilayer stabilised the capsid structure.